Free Apps or Paid Mobile Apps: Which Business Model is more Sustainable? - Juneja, Jasneet (2010)
Mobile applications ("apps‟) have recently found a huge popularity amongst the mobile developers and the end users. These apps have provided mobile developers with more options to serve the consumers that use smartphones. This report intends to provide an insight about the right pricing model of the mobile apps i.e. free app or paid apps. There have been several discussions and articles in the industry over the free or paid app issue. However, there is still a level of confusion for developers over the adoption of the right business model for the apps. Several questions are being asked such as should there be free apps or paid apps? Which is a more sustainable business model? Why are free apps being used? What are the success factors for a paid app? This report shall take the opinions of industry experts, market reports, public surveys and other online resources to answer the questions that have raised concerns for the developers. The report also performs quantitative analysis to get an understanding about the revenue from the paid and free apps. Offering customer value and incentivizing customers are keys to generating revenue. Furthermore, the apps that are in the top list of the app stores are able to generate higher revenue and therefore a detailed analysis of the top 15 paid and free apps is performed to find out the reason for their success. Finally, few recommendations with closing thoughts have been provided to end the discussion.